The Role of Social Media Marketing and Store Image in Educating Consumers and Shaping Purchase Decisions of Fresh Vegetables in Malang - Frisca Sari Suhendra; Abdul Wahib Muhaimin; Fitria Dina Riana (Jurnal Penelitian Pendidikan IPA, 2025)
The rapid development of information and communication technology has transformed business competition, including in the fresh vegetable retail sector in Malang. The main problem faced by vegetable stores is the increasingly intense competition due to the growth of stores with similar business models, requiring effective marketing communication strategies. This study aims to analyze the direct and indirect influence of Social Media Marketing and Store Image on consumer Purchase Decisions, with Purchase Intention as a mediating variable, at Warung Sayur Segar. The research employed a quantitative approach with purposive sampling involving 100 respondents who had purchased at least once and followed the store’s Instagram account. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with WarpPLS 8.0 software. The results show that both Social Media Marketing and Store Image have a positive and significant effect on Purchase Intention and Purchase Decisions. Furthermore, Purchase Intention significantly mediates the relationship between the two independent variables and Purchase Decisions. The findings conclude that social media functions not only as a marketing tool but also as an informal educational medium that enhances consumer awareness of nutrition, product quality, and healthy consumption, thereby contributing to science literacy in everyday decision making.